Ambitious and anxious how Chinese college students succeed and struggle in American higher education - Ma, Yingyi (Columbia University Press, 2020)
Over the past decade, a wave of Chinese international undergraduate students—mostly self-funded—has swept across American higher education. From 2005 to 2015, undergraduate enrollment from China rose from under 10,000 to over 135,000. This privileged yet diverse group of young people from a changing China must navigate the complications and confusions of their formative years while bridging the two most powerful countries in the world. How do these students come to study in the United States? What does this experience mean to them? What does American higher education need to know and do in order to continue attracting these students and to provide sufficient support for them?In Ambitious and Anxious, the sociologist Yingyi Ma offers a multifaceted analysis of this new wave of Chinese students based on research in both Chinese high schools and American higher-education institutions. Ma argues that these students’ experiences embody the duality of ambition and anxiety that arises from transformative social changes in China. These students and their families have the ambition to navigate two very different educational systems and societies. Yet the intricacy and pressure of these systems generate a great deal of anxiety, from applying to colleges before arriving, to studying and socializing on campus, and to looking ahead upon graduation. Ambitious and Anxious also considers policy implications for American colleges and universities, including recruitment, student experiences, faculty support, and career services
Keywords: Geschichte 2005-2025; EDUCATION / Higher; Chinese students -- Education (Higher) -- United States; Chinese students -- Education (Secondary) -- China; Chinese students -- United States; Foreign study -- Social aspects -- United States; Chinesen; Chinesischer Student; Studienerfolg; College; Hochschule; USA